An evaluation of the nutritional status of elderly with the use of the MNA questionnaire and determination of factors contributing to malnutrition. A pilot study - Małgorzata Kostecka; Monika Bojanowska (National Institute of Public Health - National Institute of Hygiene, 2021)
Background. In the elderly, nutrition significantly influences biological aging and physiological and pathological changes in the body. A balanced diet and physical activity are the key to good physical and mental health. Objective. The aim of this study was: (1) to perform nutritional screening tests in senior citizens residing in eastern Poland and (2) to evaluate the risk of malnutrition in elderly people who live with their families, seniors who live independently, and residents of nursing homes. Material and method. The Mini Nutritional Assessment (MNA) screening tool comprising a questionnaire with 22 questions and an abbreviated and survey-adapted version of the questionnaire (KomPAN) were used to investigate eating habits and self-perception of health and nutrition. A total of 398 correctly filled out questionnaires were selected and the resulting data were subjected to statistical analyses in the Statistica 10 program. Results. The BMI values of most respondents were indicative or malnutrition or risk of malnutrition, regardless of gender (mean BMI 23.88 kg/m2 ±5.08). Most overweight and obese respondents were female (p=0.0001). The observed decreased BMI values was significantly (p=0.0012, rs= 0.6714) correlated with lower food intake. Unintentional weight loss greater than 3 kg was most frequently noted in respondents living in nursing homes and living independently (p=0.0021). Eating difficulties also considerably influenced the respondents' nutritional status. The respondents' BMI values were significantly correlated (p<0.0001) with their MNA scores, the average MNA score was 21.0±4.4, (rs = 0.7293). Overweight and obese respondents were more likely to consume at least three meals daily (OR=1.87; 95% CI: 1.32-2.06; p<0.001). Conclusions. The BMI values and MNA scores of the tested subjects indicate that the majority of the surveyed respondents were malnourished or at risk of malnutrition, regardless of gender. In the present study, the residential environment significantly influenced the patients' nutritional status, in particular in respondents with impaired motor abilities and eating difficulties.